Density functional theory study on the catalytic dehydrogenation of methane on MoO3 (0 1 0) surface - Ismail Badran (1989553) (2022)
Methane conversion offers hydrocarbon building blocks of high market value, which are easier to transport than natural gas. Under non-oxidative conditions, the process can also produce clean hydrogen fuel. In this study, we explored the catalytic dehydrogenation of methane on molybdenum oxide (MoO3) surface. Periodic density functional theory calculations were performed to study the adsorption of CH4 on two different supercells of the MoO3 (010) surface. It was found that CH4 adsorption was more favorable on a smooth surface constructed of Mo and O network, rather than a surface made with dangling O atoms as thought before. A reaction mechanism for hydrogen formation was then proposed. The first energy barrier for the H-abstraction step was calculated to be 66.4 kJ/mol, which is lower than previously reported values obtained for simple MoxOy clusters. The reactions were discussed using the two-state reactivity approach, where different electronic states can play a role in the H-abstraction step. The mechanism also showed the formation of methyl radicals and ethylene, in addition to molecular hydrogen. Other Information Published in: Computational and Theoretical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.comptc.2022.113689